Analysis of rice profitability and marketing chain: the case of Fogera Woreda, South Gondar Zone, Amhara National Regional State, Ethiopia - Takele, A. (Haramaya University, 2010)
This study examined the profitability and marketing chain of rice in Fogera Woreda, South Gondar zone of Amhara Regional State. From the woreda, 14 peasant associations (PAs) producing rice were selected purposively and it is stratified based on the existing rice production farming system (upland and lowland), from each farming system two PAs were selected randomly. Then samples of respondents were selected randomly proportional to its population size. A total of 165 sample farm households were selected from the four PAs for the interview. In addition, market related data were collected from 25 assemblers (20 rural and five urban marketers) and six wholesalers and 10 millers at Woreta market, 21 retailers and five urban distributors at Bahir Dar market and 29 retailers at Gondar market. Both econometrics and descriptive analyses consistency used in this study. Results from the descriptive analysis show that wholesalers and millers are the most important buyers of rice from producers, about 45% and 27%, respectively. Farmers travel, on average, 1.6hr to the woreda market to sell their rice produce. The market concentration ratio is 0.77, showing that the rice market is oligopsonsitic. High initial capital and prior control of farmers is a barrier to entry in rice trading. Results from the Heckman’s two step selection model show that, market information access, quantity of paddy produced, total value of livestock unit and extension contact with farmers increase household’s probability of selling rice. Household head’s education level and total quantity rice produced were positively affecting the level of rice sale. However increase in family size decrease the volume of rice supply to the market per household. The Tobit result also revealed that quantity produced is jointly affected both the probability of market participation and volume of supply. The cost benefit analysis of rice production shows that rice production is a profitable business for farmers. The net income obtained from production per hectare of rice is Birr 5006.48. The cost margin indicate that producers obtain on average 35.97 Birr per qt, assemblers get 139 Birr per qt, millers a profit of 5.4 Birr per qt, wholesalers 9 Birr per qt, urban distributors birr 3.88 Birr per qt and retailers around 19 Birr per qt respectively. Though, assemblers get more profit, they also incur more marketing cost. The possible recommendations forwarded are strengthening market information and extension system, intervention to increase production and productivities by using improved agricultural inputs, promoting education and trainings about rice production and marketing and finally promoting family planning are the recommended policy implications.